Preparation and characterization of orange peels for commercial plastic: a review - Fadzil, Nur Farhan; Othman, Siti Amira (Asian Scholars Networks, 2021)
The synthetic plastic made by petroleum-based resources are commonly used by the society for their daily activities such as shopping bags, food packaging and drinking bottles. These plastics ease our daily task, however the arising amounts of their waste lead to the overloading in land and affect the environment and ecosystems due to their non-biodegradable properties. On the other side, orange juice production generates about 50-60%of residues from initial the mass that are underutilized. The orange wastes constitute a valuable bioactive compound such as pectin and cellulose, potential for bioplastic application. Thus, orange peels reinforced by the epoxy composites are investigated for the production of bio-based polymer utilized ferrite magnetic powder as filler.